Spin‐Resolved Imaging of Antiferromagnetic Order in Fe4Se5 Ultrathin Films on SrTiO3 - Zhang, Wenhao; Zhang, Zhi‐Mo; Nie, Jin‐Hua; Gong, Ben‐Chao; Cai, Min; Liu, Kai; Lu, Zhong‐Yi; Fu, Ying‐Shuang (Advanced materials (Weinheim), 2023)
Unraveling the magnetic order in iron chalcogenides and pnictides at atomic scale is pivotal for understanding their unconventional superconducting pairing mechanism, but is experimentally challenging. Here, by utilizing spin‐polarized scanning tunneling microscopy, real‐space spin contrasts are successfully resolved to exhibit atomically unidirectional stripes in Fe4Se5 ultrathin films, the plausible closely related compound of bulk FeSe with ordered Fe‐vacancies, which are grown by molecular beam epitaxy. As is substantiated by the first‐principles electronic structure calculations, the spin contrast originates from a pair‐checkerboard antiferromagnetic ground state with in‐plane magnetization, which is modulated by a spin–lattice coupling. These measurements further identify three types of nanoscale antiferromagnetic domains with distinguishable spin contrasts, which are subject to thermal fluctuations into short‐ranged patches at elevated temperatures. This work provides promising opportunities in understanding the emergent magnetic order and the electronic phase diagram for FeSe‐derived superconductors. Fe4Se5 ultrathin films are experimentally demonstrated to host a pair‐checkerboard antiferromagnetic (AFM) ground state with in‐plane magnetization, evident with magnetic‐field‐dependent spin contrasts in real‐space by spin‐polarized scanning tunneling microscopy. The AFM order is modulated by a spin–lattice coupling and exhibits three types of nanoscale AFM domains, which are subject to thermal fluctuations into short‐ranged patches at elevated temperatures.